Recent Advances of Manganese-Based Hybrid Nanomaterials for Cancer Precision Medicine - Liu, Xiaoman; Rong, Pengfei (Frontiers in Oncology, 2021)
Cancer precision medicine (CPM) could tailor the best treatment for individual cancer patient, while imaging techniques play important roles for its application. With the characteristics of non-invasion, nonionized, radiation-free, multidimensional imaging function, and real-time monitoring, magnetic resonance imaging (MRI) is a powerful techniquean effective way for early tumor detection of tumors, and it has become a tower of strength in CPM imaging techniques. Due to linkage with nephrogenic systemic fibrosis (NSF), gadolinium (Gd) based contrast agent (CA), which was long used in MRI, has been restricted by the Food And Drug Administration (FDA). In this review, we would like to introduce the manganese (Mn)-based CAs, which could significantly increase the safety of MRI CAs, by realizing more superior performance and functions simultaneously in the diagnosis and treatment of tumors. Also, recent advances of Mn-based hybrid nanomaterials for cancer precision medicine are summarized and discussed.